2020
DOI: 10.1177/0897190020927274
|View full text |Cite
|
Sign up to set email alerts
|

Essential Role of Pharmacists in Asthma Care and Management

Abstract: Asthma, a chronic respiratory disease characterized by chronic airway inflammation, bronchial hyperresponsiveness, and reversible airflow obstruction, poses a substantial economic burden on patients and caregivers alike. Moreover, the heterogeneous nature of the disease and the presence of various phenotypes make the treatment of asthma challenging and nuanced. Despite the availability of several approved pharmacological treatments, approximately half of patients with asthma in the United States experienced ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 88 publications
2
36
0
Order By: Relevance
“…Healthcare professionals interact with asthma patients in the field of respiratory health during consultations or prescription refills and have an important role in providing long-term care for effective self-management. They educate patients on their disease and inhalation medication, provide training on the use of inhalation devices, address patients’ concerns and beliefs in order to guide optimal self-management of ICS therapy ( Bridgeman and Wilken, 2021 ; Murray and O'Neill, 2018 ). However, identifying and overcoming barriers to self-management of ICS therapy is a major challenge in clinical practice ( Murray and O'Neill, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Healthcare professionals interact with asthma patients in the field of respiratory health during consultations or prescription refills and have an important role in providing long-term care for effective self-management. They educate patients on their disease and inhalation medication, provide training on the use of inhalation devices, address patients’ concerns and beliefs in order to guide optimal self-management of ICS therapy ( Bridgeman and Wilken, 2021 ; Murray and O'Neill, 2018 ). However, identifying and overcoming barriers to self-management of ICS therapy is a major challenge in clinical practice ( Murray and O'Neill, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The SMDs for IT from the pooled studies showed a significant improvement after the pharmacists’ interventions. Poor IT has been reported as one of the most problematic aspects of asthma treatment, and pharmacists have a leading role in resolving this matter 2 . The educational interventions lead to better drug and inhaler administration, and effective educational methods to promote medication adherence are recommended in community pharmacies and the whole health system.…”
Section: Discussionmentioning
confidence: 99%
“…Asthma is estimated to be involved more than 339 million people worldwide, and the condition is the most prevalent non‐communicable disease in paediatrics 1 . Treatable alas not curable, the burden of asthma is high; patient compliance ensured by communicating with the pharmacist could effectively contribute to lowering the burden, especially in chronic/persistent asthma 1,2 . However, the medication adherence and desirable inhalation methods remain poor in asthmatic patients, and the therapies may not be optimal; the pharmacists are the frontiers of the health system, and their educational interventions, monitoring, follow‐up and collaboration with the physicians seem to be one key to this matter 2,3 …”
Section: Introduction What Is Known and Objectivementioning
confidence: 99%
“…Given the increasing demands on the time of primary care doctors, particularly in the area of chronic disease management, perhaps referrals to specialists need to be considered more often or a need for greater involvement of community pharmacists or nurses. It has been repeatedly shown throughout the literature that adults with asthma have benefited from pharmacists' interventions in their asthma care [57][58][59][60]. A study by Saini et al [57] highlighted that pharmacists who deliver specialized models of asthma care to patients are also able to meet their needs.…”
Section: Discussionmentioning
confidence: 99%